Plant density and nitrogen interaction on productivity of summer sesame (Sesamum indicum L.): PLANT DENSITY AND NITROGEN INTERACTION ON PRODUCTIVITY OF SUMMER SESAME - K RAMESH; G SURESH; A AZIZ QURESHI; P RATNAKUMAR; PRADUMAN YADAV (Journal of Oilseeds Research, 2021)
Plant spacing manipulations affect the quality and quantity of sunlight for photosynthesis and the branching vis-à-vis crop productivity. Field experiment was conducted to study the effect of different plant spacings (broadcasting, 30 x 30 cm, 45 x 30 cm and 45 x 45 cm and solid rows of 45 cm apart) in conjunction with nitrogen doses (0, 30 and 45 kg/ha) on growth rate of branches and capsules, and seed yield of sesame (Variety Sweta). Branching, a significant plant phenotypic plasticity in sesame was the main attribute affected by plant spacing and N doses. Solid rows of 45 cm apart sowing (2.2 lakh plants/ha) recorded significantly the highest seed yield (8.0 q/ha) among different plant spacing treatments. Crop raised with broadcasting method (approx 2.8 lakh plants/ha) yielded 7.4 q/ha which was significantly higher than other plant spacings of 30×30 cm (1.11 lakh plants/ha), 45×30 cm (0.74 lakh plants/ha) and 45×45 cm (0.49 lakh plants/ha). Application of 45 kg N/ha recorded significantly higher seed yield than 30 kg N/ha and no N across different plant spacings. Except 45×30 cm and 45×45 cm spacings, all other spacings recorded significantly higher seed yield for each increment in N dose.